Incidental finding of a rare ureteroinguinal hernia: general surgeons take heed! - Long, Brittany; Aseervatham, Ratna (International Surgery Journal, 2022)
Ureteroinguinal hernias are a rare phenomenon where the ureter is found in the hernia sac of an inguinal hernia, with less than 150 cases reported worldwide. They can be asymptomatic or symptomatic, and are commonly found perioperatively. We present a case of a 74-year-old man who was initially referred for consideration of surgery of bilateral inguinal hernias. The patient was relatively asymptomatic and given comorbidities the risk of surgery outweighed the benefits and he was discharged from the clinic. He was re-referred to general surgery after he sustained a fall, and subsequent computer tomography (CT) imaging of his abdomen demonstrated a right inguinal hernia containing the right distal ureter, resulting in ureteric obstruction and hydronephrosis. He subsequently underwent an open right inguinal hernia repair where the ureter was not able to be identified, but was safeguarded with blunt dissection techniques. Post operatively his renal function was stable. Ureteroinguinal hernias are most commonly found perioperatively, and therefore are at risk during dissection. Preoperative CT imaging is invaluable in the detection of ureteroinguinal hernias, and can help in the safeguarding of the ureter during operation. While a clinical diagnosis is usually all that is required for decision-making for an inguinal hernia repair; the surgeon should consider the addition of radiological work-up when the patient presents with atypical symptoms, or the hernia sac may contain intra-abdominal structures. This will ensure correct diagnosis of the contents and subtype of inguinal hernia, and help prevent iatrogenic injury.